(untitled) - Prof. Dr. Frank Schulz-Nieswandt, Universität Köln (geschäftsführend); Prof. Dr. Thomas Lenk, Universität Leipzig; Prof. Dr. Holger Mühlenkamp, Deutsche Universität für Verwaltungswissenschaften Speyer; Prof. Dr. Johann Christian Pielow, Ruhr-Universität Bochum; Prof. Dr. Christina Schaefer, Helmut Schmidt Universität, Universität der Bundeswehr Hamburg; Prof. Dr. Ludwig Theuvsen, Georg-Augustin-Universität Göttingen; Prof. Dr. Dieter Kurt Tscheulin, Albert-Ludwigs-Universität Freiburg (ZögU Zeitschrift für öffentliche und gemeinwirtschaftliche Unternehmen, 2009)
Journal for Pu blic and Nonprofit Services is a multidisciplinary scientific journal. It provides information, discussions and documentations, and is furthermore the organ of the Federal Public Services - German Section of CEEP e. V. The journal offers comprehensive information on the important area of public companies and provides a forum for practitioners and researchers. It is dedicated to federal, state, and local companies, mixed-economy companies, companies of trade unions, chambers, churches, political parties, foundations and associations, publicly committed companies, cooperative companies and, in particular, enterprises of the independent welfare work. The Journal is a forum for economic, political, and social scientists and legal scholars. The publication of papers and short contributions are examined by a scientific anonymous review process that guarantees a consistently high quality of contributions. Website: www.zoegu.nomos.de